INCREASING STUDENTS’ INTEREST IN ENGLISH LANGUAGE LEARNING THROUGH INTERACTIVE ACTIVITIES AT JUNIOR HIGH SCHOOL STUDENTS - Mulis; Farida, Nur (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2025)
This research was Classroom Action Research (CAR). This was conducted to solve the students’ problem with English learning. The students mostly did not have a high interest in joining this subject. The subject research was 27 students 7 grade at SMP Ma’wattaibin. The research purpose was to increase the students’ interest in English learning. This research was done in 3 cycles. The first and second cycles consisted of three meetings, and the third cycle consisted of two meetings. A preliminary survey and a survey of each cycle were conducted. These surveys were done to compare the students’ interest before and after taking action. The findings revealed average of students’ interest in the preliminary survey was 12%. This indicated the low students’ interest in English learning. Then, first cycle showed that the average student interest improved, which was shown by 50% of students being interested in learning English using interactive activities. Yet, the second cycle revealed that the average of students’ interest in English learning was 70%. This current research underlines that teaching English should be constructed by interactive activities in which the students are actively involved, not monotonous methods.